Aedes aegypti CLIPB9 activates prophenoloxidase-3 in the presence of CLIPA14 after fungal infection - Ji, Yannan; Lu, Tengfei; Zou, Zhen; Wang, Yanhong (Frontiers in Immunology, 2022)
Melanization is an integral part of the insect defense system and is often induced by pathogen invasion. Phenoloxidases (POs) are critical enzymes that catalyze melanin formation. PO3 is associated with the antifungal response of the mosquito, Aedes aegypti, but the molecular mechanism of the prophenoloxidase-3 (PPO3) activation is unclear. Here we report that PPO3 cleavage activation is mediated by a clip-domain serine protease, CLIPB9. We purified recombinant CLIPB9 and found that it cleaved PPO3 and increased PO activity in the hemolymph. We then identified CLIPA14 (a serine protease homolog) by co-immunoprecipitation using anti-CLIPB9 antibody. After being cleaved by CLIPB9, Ae. aegypti CLIPA14 acted as a cofactor for PPO3 activation. In addition, dsRNA co-silencing of CLIPB9 and CLIPA14 genes reduced melanization after infection with the entomopathogen, Beauveria bassiana, making the adult mosquitoes more sensitive to fungal infection. These results illustrate the roles of CLIPB9 and CLIPA14 in the PPO activation pathway and revealed the complexity of the upstream serine protease network controlling melanization.